2011
DOI: 10.1111/j.1524-4725.2010.01819.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrocautery and Computerized Bipolar Coagulation Simplify Nail Surgery

Abstract: The authors have indicated no significant interest with commercial supporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…5,9 ED uses electric current to generate heat and cause tissue dehydration and superficial destruction, thereby inducing coagulation necrosis and carbonization of cells, which are then ultimately removed via a combination of enzymatic degradation and phagocytosis. 13,17 The amount of ED needed can be reduced when most of the matrix tissue is first removed by an adjunct method such as dissection or curettage. 13 Recurrence rates following ED from the 11 studies in this review ranged from 0% to 44.8%, however, 7 out of the 11 studies reported a recurrence rate of 0% to 5%, and 2 out of the 11 studies, 10% to 15%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,9 ED uses electric current to generate heat and cause tissue dehydration and superficial destruction, thereby inducing coagulation necrosis and carbonization of cells, which are then ultimately removed via a combination of enzymatic degradation and phagocytosis. 13,17 The amount of ED needed can be reduced when most of the matrix tissue is first removed by an adjunct method such as dissection or curettage. 13 Recurrence rates following ED from the 11 studies in this review ranged from 0% to 44.8%, however, 7 out of the 11 studies reported a recurrence rate of 0% to 5%, and 2 out of the 11 studies, 10% to 15%.…”
Section: Discussionmentioning
confidence: 99%
“…5,9 ED uses electric current to generate heat and cause tissue dehydration and superficial destruction, thereby inducing coagulation necrosis and carbonization of cells, which are then ultimately removed via a combination of enzymatic degradation and phagocytosis. 13,17 The amount of ED needed can be reduced when most of the matrix tissue is first removed by an adjunct method such as dissection or curettage. 13…”
Section: Discussionmentioning
confidence: 99%